2020
DOI: 10.1002/jmrs.438
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions and preferences about prostate fiducial markers and ultrasound motion monitoring procedures in radiation therapy treatment

Abstract: Introduction Patient experiences and preferences of image‐guidance procedures in prostate cancer radiotherapy are largely unknown. This study explored experiences and preferences of patients undergoing both fiducial marker (FM) insertion and Clarity ultrasound (US) procedures. Methods A sequential explanatory mixed method approach was used. A questionnaire (n = 40) ranked experiences from 0 to 10 (worst) in the domains of invasiveness; pain; physical discomfort; and psychological discomfort. Responses were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…This present study builds upon two previous studies [15] , [16] . The first study captured the perspectives and preferences of 22 prostate cancer patients regarding image-guidance related procedures (fiducial markers versus transperineal ultrasound) via semi-structured interviews [15] .…”
Section: Introductionsupporting
confidence: 61%
“…This present study builds upon two previous studies [15] , [16] . The first study captured the perspectives and preferences of 22 prostate cancer patients regarding image-guidance related procedures (fiducial markers versus transperineal ultrasound) via semi-structured interviews [15] .…”
Section: Introductionsupporting
confidence: 61%
“…Though clinical staff can assess anatomical compression with measures such as the PICS distance or CPR, Pang et al (2017) concluded inter-observer variation with the Clarity system whilst minimal, appeared to be influenced by training and/or level of experience [22]. It is also expected that the avoidance of excessive compression will aide in continued patient comfort and tolerability [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Intrafraction monitoring prevents surrounding organs at risk (OAR) from receiving higher doses and maintains the treatment intent according to the medical prescription [6]. The TPUS and associated set up is reported to be well-tolerated by patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a clinical result, Kaneda et al 83 reported a significantly lower positioning error when performing image guidance of external beam radiotherapy by matching golden fiducials instead of bone matching in a retrospective analysis of a series of 38 patients presenting intermediate-or high-risk prostate cancer and received EBRT following LDR brachytherapy. Interestingly, Brown et al 84 analyzed patient's experiences and preferences of imageguidance procedures, exploring the different perceptions about the placement of fiducial markers versus the use of ultrasound for image guidance of radiotherapy. Forty questionnaires were administrated to patients, with the aim to deepen: invasiveness, pain, physical discomfort, and psychological discomfort; moreover, 22 interviews further investigated insights into their perspectives and preferences.…”
Section: The Most Intriguing Inter-and Intra-fractional Treatment Aids For Modern Gating Of the Image-guided Radiotherapy: Fiducial Markementioning
confidence: 99%